Functional miR-142a-3p Induces Apoptosis and Macrophage Polarization by Targeting tnfaip2 and glut3 in Grass Carp (Ctenopharyngodon idella) - Tao, Lizhu; Pang, Yifan; Wang, Anqi; Li, Lisen; Shen, Yubang; Xu, Xiaoyan; Li, Jiale (Frontiers in Immunology, 2021)
During microbial invasion, an inflammation response is induced to eliminate the pathogen. However, un-controlled or un-resolved inflammation can lead to tissue damage and death of the host. MicroRNAs (miRNAs) are the signaling regulators that prevent the uncontrolled progress of an inflammatory response. Our previous work strongly suggests that miR-142a-3p is closely associated with immune regulation in grass carp. In the present study, tnfaip2 and glut3 were confirmed to be the target genes of miR-142a-3p as verified by expression correlation analysis, gene overexpression, and dual luciferase reporter assay. By targeting tnfaip2 and glut3, miR-142a-3p regulates cell viability and stimulates cell apoptosis. In addition, it may be involved in macrophage polarization. Our results suggest that miR-142a-3p has multiple functions in host anti-bacterial immune response. Our study provides further understanding of the molecular mechanisms between miRNAs and their target genes and novel insights into developing pro-resolution strategies in the treatment of complex inflammatory diseases in fish.